Episodes toward a Fluxarchitecture. The work of George Maciunas, Shadrach Woods and Joachim Pfeufer - Doglio, Federica (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
Fluxus, an artistic movement that emerged in 1960, crossed borders within the arts. Soon it expanded to include sculpture, poetry, performance, photography, and cinema, taking on a multi-disciplinary character that regularly crossed or erased borders within the arts. Its relationship to architecture, however, is more complex. In the 1960s, a few architects sought to resolve contradictions between the principles of Fluxus and the presumptions of their own field, and explored the possibilities of change —flux— in architectural practice. This article will investigate possible connections between Fluxus and the architectural practices. It considers three figures who were both theorists and architects: Georges Maciunas, Shadrach Woods and Joachim Pfeufer. Their practices, considered together, form what in this article I coin “fluxarchitecture”.